Prevalence of thalassemia and hemoglobinopathy in antenatal mothers with relation to complete hemogram and high performance liquid chromatography-a hospital based study of Eastern India - Roy Chowdhury, Anadi; Talukdar, Manas (International Journal of Research in Medical Sciences, 2018)
Background: Iron deficiency anemia (IDA) and Beta thalassemia (BT) are two most common causes of microcytic hypochromic anemia in our country affecting the reproductive age group. It is important to discriminate between these two entities to prevent treatment with iron of individuals with thalassemia trait as well as prevent homozygous transmission of B thalassemia trait (BTT). Aim of the study was to investigate causes of microcytic anemia in antenatal mothers and to find out the role of Cell Counter and High Performance Liquid Chromatography (HPLC) so as to screen BTT and other hemoglobinopathies. Methods: This study was done over a period of six months (May 2017 to October 2017) in the Department of Pathology in R. G. Kar Medical College. We analyzed the blood samples of all antenatal mothers attending Department of Pathology for blood tests and a complete hemogram and hemoglobin A2 (Hb A2) quantitation was done. Results: Total cases evaluated were 2200 of which 442 patients were found to have microcytic hypochromic anemia (MCV<80%, MCH<27). Rest that is 1758 was normal. Of 442 cases of microcytic hypochromic anemia, 205 were found to have IDA, 115 BTT, 112 E trait, 1 case each of Hemoglobin E disease, E-Beta thalassemia and hereditary persistence of fetal hemoglobin (HPFH). Hemoglobinopathies like S trait and Hemoglobin J (Hb J) was found in 4 and 3 cases respectively. Conclusions: In India, Microcytic hypochromic anemia is common and may be due to IDA, BTT or other hemoglobinopathies Cell counter-based parameters and formulas, along with HPLC can be an effective method of thalassemia screening in a society.